Managing an Environmental-Friendly Coal Mining Wastewater Processing - Muhammad Naswir; Ria Purnama Sari (Jurnal Inovasi Teknologi, 2020)
Jambi is one of the provinces in Indonesia that has an abundance coal potential. One of the companies that holds the Mining-Business License (IUP) for Coal mining production and operations is PT. XYZ, which is chosen to be the source of samples for this research. One of the negative impacts caused by coal mining activities is the wastewater emerge from both mining and stockpile activities. Unprocessed wastewater can pollute the environment, particularly the surface water and ground water around the mining site. Materials utilized in managing coal mine wastewater in this research are bentonite (natural and activated) and limestone from clamshells. Bentonite is expected to be able to absorb TSS, Fe, Mn and Hg values, while clamshells to increase the pH value in coal mine wastewater. This research aims to determine the ability of clamshell bentonite and limestone in processing coal mine wastewater. The samples in this research are amounted to 19 consisting of 1 control sample and 18 treatment samples. The treatments are made in 6 mass variations and 3 variations of contact time. A combination of 1 gram of material is contacted with 250 ml of coal mine wastewater. The characteristics of coal mine wastewater from PT. XYZ based on the samples taken are as follows: pH 4,40, TSS 66 mg/l, Fe 0,998 mg/l, Mn 7,340 mg/l, dan Hg 0,00076 mg/l. The results of this research show that the compilation of bentonite and limestone from clamshells is able to reduce the parameters of coal mine wastewater. The absorption efficiency of the compilation of bentonite and limestone in decreasing the parameters of coal mine wastewater has varied values with the average of: pH 68,62%, TSS 90,91%, Fe 97,60%, Mn 26,71%, and Hg 96,05%. Mass variations and contact time influence the decrease in coal mine wastewater parameters. The treatment on variations of 0.75 grams of activated clamshell bentonite and 0.25 grams of clamshell limestone with 30 minutes contact time is the treatment that produces wastewater that meets the environmental quality standards, which are pH 7,16 from 6 – 9 of environmental quality standards value, TSS 6 mg/l from 400 mg/l of environmental quality standards value, Fe < 0,02 mg/l from 7 mg/l of environmental quality standards value, and Hg < 0,00003 mg/l from 0,002 mg/l of environmental quality standards value. With good management, it is expected that the impacts caused by waste water from coal mining can be minimized in order to achieve environmentally friendly mining activities